2016
DOI: 10.4238/gmr.15038624
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in natural populations of mangaba in Sergipe, the largest producer State in Brazil

Abstract: ABSTRACT. Mangaba (Hancornia speciosa Gomes) is found in areas of coastal tablelands in the Brazilian Northeast and Cerrado regions. This species has been subjected to habitat fragmentation that is mainly due to human activity, and requires conservation strategies. The aim of this study was to analyze the structure and inter-and intrapopulation genetic diversity of natural populations of H. speciosa Gomes using inter-simple sequence repeat (ISSR) molecular markers. A total of 155 individuals were sampled in 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 28 publications
0
31
0
11
Order By: Relevance
“…It occurs in the tableland and coastal plains of the Northeast, in the Cerrado of the Central-West, in the North and Southeast regions of Brazil. The state of Sergipe is the largest mangaba producer in the country, especially in the municipalities of Barra dos Coqueiros, Itaporanga D'Ajuda, and Estância (Soares et al, 2016). The deforestation of large areas of natural occurrence of the species provides the genetic erosion of mangaba, and associated with this, the unsustainable use of remaining individuals result in irreparable environmental damage (Santos et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It occurs in the tableland and coastal plains of the Northeast, in the Cerrado of the Central-West, in the North and Southeast regions of Brazil. The state of Sergipe is the largest mangaba producer in the country, especially in the municipalities of Barra dos Coqueiros, Itaporanga D'Ajuda, and Estância (Soares et al, 2016). The deforestation of large areas of natural occurrence of the species provides the genetic erosion of mangaba, and associated with this, the unsustainable use of remaining individuals result in irreparable environmental damage (Santos et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Each cycle the specimens suffered a chain reaction of denaturation at 94 °C for one minute, girdling at various temperatures for 45 seconds and, finally, extension at 72 °C for two minutes (Soares et al, 2016).…”
Section: Analysis Of Genetic Diversitymentioning
confidence: 99%
“…Therefore, inside the germplasm bank progenies hybridization may occur due to natural pollinator agents. Soares et al (2016) carried out the test with 155 mangaba individuals of natural species from Sergipe, concluding 100% of polymorphism presenting high genetic variability among populations. The rate of genetic similarity of this study was considered low when compared with the study on natural species, the fact of the matrices belonging to the BAG, factors such as geographical proximity of the accessions and the position of the matrices in the experimental field, interfere in genetic diversity between matrix/progeny.…”
Section: Molecular Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The RAPD , ISSR (Soares et al, 2016;Amorim et al, 2013) and SSR molecular markers have been reported as showing genetic diversity in mangaba trees. The studies using SSR markers in natural populations and in BagMangaba entries use primers developed by Rodrigues et al (2015).…”
Section: Genetic Diversitymentioning
confidence: 99%